2010
DOI: 10.1017/s0033291710000255
|View full text |Cite
|
Sign up to set email alerts
|

A latent profile analysis of the typology of bulimic symptoms in an indigenous Pacific population: evidence of cross-cultural variation in phenomenology

Abstract: Background Previous efforts to derive empirically based eating disorder (ED) typologies through latent structure modeling have been limited by ethnic and cultural homogeneity of their study populations and their reliance on DSM-IV ED signs and symptoms as indicator variables. Methods Ethnic Fijian schoolgirls (N = 523) responded to a self-report battery assessing ED symptoms, herbal purgative use, comorbid psychopathology, clinical impairment, cultural orientation, and peer influences. Participants who endor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 40 publications
2
9
0
3
Order By: Relevance
“…Several studies have identified subgroups of individuals resembling those with BN that are characterized by binge-eating and purging symptoms in both clinical and community populations by using latent class analysis (LCA) [30][31][32][33][34][35][36][37] or latent profile analysis (LPA) [38][39][40][41][42][43][44][45]. Latent class analysis seeks to identify the smallest number of identifiable latent classes (i.e., categories of a latent factor) that account for the association between three or more observed dichotomous and polychotomous variables [46,47].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have identified subgroups of individuals resembling those with BN that are characterized by binge-eating and purging symptoms in both clinical and community populations by using latent class analysis (LCA) [30][31][32][33][34][35][36][37] or latent profile analysis (LPA) [38][39][40][41][42][43][44][45]. Latent class analysis seeks to identify the smallest number of identifiable latent classes (i.e., categories of a latent factor) that account for the association between three or more observed dichotomous and polychotomous variables [46,47].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, LPA is used to determine latent classes from observed continuous variables. Of those studies conducted with participants with bulimic symptoms, four have identified coherent groupings of patients on the basis of bulimic and purging symptoms [33][34][35]42], one on the basis of six impulsive behaviors [48], and three on the basis of psychological and interview measures of co-morbid psychopathology [37,38,45]. Among them, only one study replicated the previous multi-impulsivity bulimic classification empirically [48]; nevertheless, the issue of how behavioral symptoms of eating and impulsivity co-exist within individuals was seldom addressed in these studies.…”
Section: Introductionmentioning
confidence: 99%
“…Terdapat 142 (70,6%) responden yang memiliki persepsi tubuh negatif. Hal ini tidak sesuai dengan penelitian yang dilakukan oleh Thomas et al (22) bahwa sebagian besar responden memiliki persepsi tubuh yang positif, hal ini mungkin disebabkan terdapat perbedaan kategori usia dengan yang dilakukan oleh peneliti yaitu pada penelitian Thomas et al (22) sebagian besar responden adalah dewasa muda dan memiliki kepercayaan diri yang tinggi sehingga dalam setiap kategori status gizi, sebagian besar memiliki persepsi tubuh yang positif. Hasil penelitian yang dilakukan oleh peneliti menyatakan bahwa sebagian besar responden memiliki persepsi tubuh yang negatif, hal ini didukung oleh penelitian yang dilakukan oleh Bully et al (23) , hal ini mungkin disebabkan pada penelitian Bully et al (23) dan penelitian ini sama-sama menggunakan kuesioner dan responden yang diteliti memiliki kategori usia yang sama yaitu pada kategori usia remaja.…”
Section: Pembahasanunclassified
“…Apenas Marisol citou uma dieta restritiva. O comportamento alimentar compulsivo vem sendo identificado como mais presente entre mulheres e homens negros com risco para transtorno alimentar em vários estudos internacionais [38][39][40] realizados para tentar compreender a diferença de manifestação dessa desordem entre grupos diversos etnicamente, enquanto a restrição alimentar vem sendo relacionada com as caucasianas.…”
Section: 36-38unclassified
“…Isso comunga com a ideia de Csordas, de que a abordagem fenomenológica, na qual "o corpo não é um objeto a ser estudado em relação à cultura, mas é o sujeito ou base existencial da cultura", 40 seria a mais interessante para entender o paradigma da corporeidade. Ele se baseia nas visões de Merleau Ponty sobre a percepção do corpo indo além da dualidade sujeito/objeto, visto que há sempre mais do que é possível perceber através dos olhos, e do entendimento de Bourdieu, de que o corpo socialmente informado, ou seja, o habitus, é o princípio gerador e unificador de todas as práticas sociais.…”
unclassified